Strategi guru dalam mengatasi kesulitan membaca pada kelas rendah - nur, zikrina Khalifa; Haifaturrahmah, Haifaturrahmah; Fujiaturrahman, Sukron (Jurnal Ilmiah Telaah, 2026)
Reading is a fundamental skill that forms the foundation of the learning process, yet many lower-grade elementary school students still face difficulties in reading. This article aims to examine teachers’ strategies in overcoming reading difficulties among lower-grade students through a library research method with a qualitative approach. Data were collected from literature including books, journals, articles, and previous studies relevant to reading difficulties and teaching strategies. The findings show that reading difficulties can be caused by both internal and external factors, such as lack of early literacy stimulation, monotonous teaching methods, and limited parental support. Strategies that teachers can apply include the use of phonics methods, multisensory approaches, educational games, and the creation of a supportive learning environment. Moreover, collaboration between teachers and parents is essential to strengthen students’ reading skills. With innovative, motivational, and collaborative strategies, lower-grade students are more likely to overcome reading barriers and achieve better academic performance.